2014
DOI: 10.2138/am-2015-5001
|View full text |Cite
|
Sign up to set email alerts
|

Phase relationships in the system K2CO3-CaCO3 at 6 GPa and 900-1450  C

Abstract: Phase relations in the system K 2 CO 3 -CaCO 3 have been studied in the compositional range, X(K 2 CO 3 ), from 100 to 10 mol%, at 6.0 GPa and 900-1450 °C. At 900-950 °C, the system has three intermediate compounds:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 89 publications
(104 reference statements)
2
27
1
1
Order By: Relevance
“…The results indicate that the melting temperature of K 2 CO 3 is 1220 ± 20°C at 4.0 ± 0.5 GPa, 1195 ± 15°C at 5.0 ± 0.5 GPa, 1290 ± 10°C at 9.0 ± 0.5 GPa, and 1313 ± 10°C at 11.5 ± 0.5 GPa. Shatskiy et al (2015) reported that the melting temperature of K 2 CO 3 at 6 GPa is about 1425°C, which is about 225°C higher than those at 5 GPa determined in this study. Thus far, the difference has been difficult to explain.…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…The results indicate that the melting temperature of K 2 CO 3 is 1220 ± 20°C at 4.0 ± 0.5 GPa, 1195 ± 15°C at 5.0 ± 0.5 GPa, 1290 ± 10°C at 9.0 ± 0.5 GPa, and 1313 ± 10°C at 11.5 ± 0.5 GPa. Shatskiy et al (2015) reported that the melting temperature of K 2 CO 3 at 6 GPa is about 1425°C, which is about 225°C higher than those at 5 GPa determined in this study. Thus far, the difference has been difficult to explain.…”
Section: Resultscontrasting
confidence: 69%
“…Thus far, the difference has been difficult to explain. One possible reason is that Shatskiy et al (2015) determined the melting of K 2 CO 3 from an image. In such a case, overestimation of the melting temperature is easy because of the unobvious difference between the separate melt and solid of K 2 CO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 (Shatskiy et al, 2014), Na2CO3 -FeCO3 (Shatskiy et al, 2015a), and K2CO3 -CaCO3 (Shatskiy et al, 2015b) binaries at 6 GPa, in addition to the study of Buob et al (2006) on the MgCO3 -CaCO3 binary at 6 GPa.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…The EDS spectra were optimized for the quantification using standard XPP procedure included in the INCA Energy 450 software. Calibrated EDS spectra from the used device were reported to be of the same quality as wavelength dispersive analysis in many recent works …”
Section: Methodsmentioning
confidence: 99%